Bakteri Endofit Pinang Sebagai Penghasil Antioksidan dan Inhibitor α-Glukosidase - Balkis, Tiara; Fachrial , Edy; Wienaldi, Wienaldi (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Diabetes mellitus is a chronic metabolic disorder with a high global prevalence and serious complications. The prediabetes stage is a critical target for prevention, often managed with α-glucosidase inhibitors. However, synthetic drugs such as acarbose are frequently associated with gastrointestinal side effects, highlighting the need for safer alternatives. Endophytic microbes from medicinal plants, including areca nut (Areca catechu), have the potential to produce bioactive compounds with antioxidant and antidiabetic activities. Objective: This study aimed to explore endophytic bacteria from fresh areca nut seeds as a source of metabolites with antioxidant and α-glucosidase inhibitory activity. Methods: Fresh areca nut seeds were sterilized using the surface sterilization method, followed by endophytic bacterial isolation and Gram staining. Cultures were fermented in Nutrient Broth, and supernatants were obtained by centrifugation. Antioxidant activity was assessed using the DPPH method, while α-glucosidase inhibition was tested in vitro with p-nitrophenyl α-D-glucopyranoside as substrate. Acarbose served as the positive control. Results: Seven Gram-negative, rod-shaped endophytic isolates (BP1-BP7) were obtained. Isolate BP1 exhibited the highest antioxidant activity with 45.7% inhibition. Furthermore, the BP1 supernatant demonstrated potent α-glucosidase inhibitory activity up to 93,6%, comparable to that of acarbose (91%). Conclusion: Endophytic bacteria from areca nut seeds possess dual bioactivity as antioxidants and α-glucosidase inhibitors, suggesting their potential as sustainable alternative antidiabetic agents worthy of further investigation.